HERO WITH ZEROES?: Tensions of Using an Anti-Discrimination Framework and an Impact Case Approach for Disability Rights Advocacy in China - Ma, Zhiying; Ni, Zhen (Disability Studies Quarterly, 2020)
In 2014, a blind massage therapist named Li Jinsheng took the National College Entrance Examination (NCEE) in Braille, the first to do so in China. To everyone's surprise, he turned in blank answer sheets for two of the four subjects, which generated strong criticisms from the general public and blind communities. This article examines the conditions, process, and aftermaths of this event to consider what it means to use an anti-discrimination framework and an impact case approach for disability rights advocacy. Data comes from observation of media representations and discussions, interviews with key actors and stakeholders, and a focus group with blind college students. Our analysis of Li's case shows that in China, anti-discrimination actions often take the form of using individual cases to attack single, identifiable policy barriers, and they are typically carried out by people who are not directly impacted by the state's paternalistic biobureaucracy or the vulnerabilities it generates. As such, these cases might not sufficiently represent the desires and struggles of most people with disabilities, and the individualistic approach might further alienate the disabled communities. While effective in dismantling the particular policy barrier, such anti-discrimination actions may fall short of addressing more systemic, structural issues. This article ends with reflections on the tensions in using anti-discrimination impact cases in China and beyond, and on how to work on deeper struggles and build broader alliances in disability rights advocacy.